“My Volleyball” Android-based Volleyball Learning Media for High School Students - Ibnu Fatkhu Royana; Irwan Muhammad Baihaqi; Galih Dwi Pradipta (Proceeding International Conference on Digital Education and Social Science, 2024)
The purpose of this research is to develop Android-based Volleyball Basic Techniques Learning Media for high school students. The research method uses the development method. Validation was carried out by material experts and media experts. The subjects of this study were students of SMKN 1 Kalinyamatan Jepara, with a population of 198 students consisting of 32 students as a small-scale trial and 166 students as a large-scale trial. Data collection used an instrument in the form of a questionnaire. Data analysis using descriptive quantitative generated in the form of percentages. The results showed that the material expert validation results get an average score of 79.125% and fall into the good category. The results of media expert validation get an average score of 84.75 and fall into the excellent category. In the small-scale product trial, the average assessment results were 87.75% and included in the very good category. While in the large-scale trial getting an average assessment of 85.92% and included in the very good category. The conclusion in this study is that the development of learning media "My Volleyball" is feasible to use as a learning media for basic volleyball techniques for high school students.